2006
DOI: 10.2139/ssrn.2281861
|View full text |Cite
|
Sign up to set email alerts
|

Consumer's Attitudes and Willingness-to-Pay for Green Food in Beijing

Abstract: A survey in random-selected supermarkets in Beijing, the capital city of China, is reported to identify the attitudes and perceptions of consumers toward green-labeled milk, as well as their willingness to pay (WTP) for it, and to determine the factors that affect their WTP. The study reveals that the majority of households are quite familiar with green food and most of them take positive attitudes towards them, while with certain anxieties. Both remarkable preferences for location and branding in milk purchas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
1
15
0
4
Order By: Relevance
“…A study by Zhu et al, (2013) found that income and education influence green-food purchase intentions and behaviours. Chinese studies report that gender -being female -is an important demographic variable, along with income, education and family size, that influences willingness to pay for green food (Xia and Zeng, 2007;Xia and Zeng, 2008). Studies on Western consumers show that concern for young children is likely to increase organic food consumption (Kriwy and Mecking, 2012); the organic food buyer is likely to be female (Lockie et al, 2004), female with children (Dettmann and Dimitri, 2009;Van Doorn andVerhoef, 2011) and is likely to be highly educated (Govidnasamy and Italia, 1990;Kriwy and Mecking, 2012).…”
Section: Discussion and Contributions To The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A study by Zhu et al, (2013) found that income and education influence green-food purchase intentions and behaviours. Chinese studies report that gender -being female -is an important demographic variable, along with income, education and family size, that influences willingness to pay for green food (Xia and Zeng, 2007;Xia and Zeng, 2008). Studies on Western consumers show that concern for young children is likely to increase organic food consumption (Kriwy and Mecking, 2012); the organic food buyer is likely to be female (Lockie et al, 2004), female with children (Dettmann and Dimitri, 2009;Van Doorn andVerhoef, 2011) and is likely to be highly educated (Govidnasamy and Italia, 1990;Kriwy and Mecking, 2012).…”
Section: Discussion and Contributions To The Literaturementioning
confidence: 99%
“…The number of studies conducted on Chinese consumers and organic food is growing (Roberts and Rundle-Thiele, 2007;Yin, Wu, Du and Chen, 2010;Sirieux et al, 2011;Bing et al, 2011;Lobo and Chen, 2012;Marchesini et al, 2012;Thøgersen and Zhou, 2012;Thøgersen et al, 2015;Yip and Janssen, 2015). The literature shows that gender, age, family size and average household income per year are the main socio-economic factors influencing willingness to pay for green food (Xia and Zeng, 2007;Xia and Zeng, 2008). Research on Western consumers indicates that organic food buyers exist across all demographic segments, with some small trends being evident.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, the transference of consumer perspectives from conventional to sustainable agro-food consumption is representative of accumulated social norm shifting, which often involves many intangible elements of decision making [8]. Although organic foods are considered mainstream now, previous papers have reported that consumers' attitudes towards sustainable food consumption and purchasing behavior are not consistent [2,9]. Therefore, this research aimed to contribute its findings by exploring consumers' perspectives on sustainable agro-food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers trust sustainable brands because they think of sustainable features in the product (Thogersen et al, 2012) and, in many cases, they are ready to pay a premium price for a product marked with credible sustainable labelling provided they understand clearly the economic and ecological beneits of the product and are able to trace these beneits to tangible evidence (Owusu and Anifori, 2013;Xia and Zeng, 2006;Xu et al, 2012). An increasing number of consumers tend to trust their own consciousness about health and the environment, and the certiications and labelling of the product constituents in making decisions for purchasing (Kai et al, 2013).…”
Section: Introduction: Emerging Sustainable Consumption Within the Frmentioning
confidence: 99%